Pengaruh Komitmen Kerja dan Komunikasi Terhadap Kinerja Pegawai Melalui Intellectual Capital - Akbar, Herawati; Dinarjo Soehari, Tjiptogoro (Dinasti International Journal of Management Science, 2024)
This research aims to identify and analyze the factors that influence employee performance including: work commitment, communication, and intellectual capital at OJK. This research method used quantitative descriptive using Structural Equation Modeling (SEM) Partial Least Square (PLS) (SEM-PLS). The population of this study is 225 organic employees of the Department of Organization and Human Resources and the Administration Section in the Field of Strategic Management I and Strategic Management II. The sample used was 100 employees, the sampling used in this study is Simple Random Sampling and has filled in 40 item questionnaire distributed online. The results of this study show that work commitment and communication have a direct positive and significant effect on intellectual capital. Work commitment does not have a direct effect on employee performance. Communication has a direct positive and significant effect on employee performance. Intellectual capital has a positive and significant effect on employee performance and is able to play a mediating role in work commitment and communication on employee performance.